Measuring the Effectiveness of E-mail Marketing toward Consumer Decision Journey at Bhinneka.com - Namira, Shastya Rizka; Wandebori, Harimukti (Journal of Business and Management, 2016)
Abstract. The rapid growth of internet-based electronic commerce makes a higher acceptance of online transactions by consumers. BHINNEKA.com is one of many information and technology (IT) online retailer that engaged in the e-Commerce industry in Indonesia. A major difficulty for marketing professionals with today's e-mail marketing is to distinguish whether the message actually reaches the right target audience at the utmost quality of the contents. The topic, which is intended to be measured, is if any associations between BHINNEKA.com’s email marketing toward each of consumer decision journey phase can be found. This study revealed key factors of e-mail marketing – subject line, incentive, length of e-mail, number of hyperlinks, and frequency jointly and separately have a positive and significant influence on consumer decision journey. Then, using the simple linear analysis this study also revealed that e-mail marketing does influence each of the consumer decision journey phase especially within the Active Evaluation phase. This result became an added value to the previous study that has not discussed the relationship yet. Moreover, this result might help Bhinneka.com to improve its digital marketing strategy such as e-mail marketing in order to compete effectively.Keywords: e-mail marketing, consumer decision journey, e-commerce, customer retention, key factors of e-mail marketing